If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 63 + -2x = 7x + 23 Reorder the terms: 63 + -2x = 23 + 7x Solving 63 + -2x = 23 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 63 + -2x + -7x = 23 + 7x + -7x Combine like terms: -2x + -7x = -9x 63 + -9x = 23 + 7x + -7x Combine like terms: 7x + -7x = 0 63 + -9x = 23 + 0 63 + -9x = 23 Add '-63' to each side of the equation. 63 + -63 + -9x = 23 + -63 Combine like terms: 63 + -63 = 0 0 + -9x = 23 + -63 -9x = 23 + -63 Combine like terms: 23 + -63 = -40 -9x = -40 Divide each side by '-9'. x = 4.444444444 Simplifying x = 4.444444444
| 50x=-2500 | | 0x^2-5x^2= | | 5-7x=95-42x | | -144-7x=9x+16 | | 8x-5x^2+2x= | | 4x+6=-60-7x | | 5x*3x^2= | | 9-9x=69-37x | | 46=f-19 | | 5x*2x= | | d-19=-46 | | 5m=3m+8 | | 25=r+7 | | 2y^2-x-4y+3=0 | | -3.281x^2=16x^2 | | 4x-(8-3x)=8x-1 | | -3x-1=3x-3 | | 15x=14x | | -3x-x=3x-3 | | 3z=5z+20 | | 4(a+24)=64 | | r-7=-13 | | 16+s=5 | | x+4=2x+6 | | 8-5(2x-7)=6 | | 3(2x+5)=30 | | 5-8(2x-7)=6 | | t+43=28 | | 5x+3y=-8(6xy+7y) | | 3x-5y=25 | | k+2K+3K-k=-100 | | -9=-4+a |